2020
DOI: 10.3389/fnagi.2020.00260
|View full text |Cite
|
Sign up to set email alerts
|

CISD2 Attenuates Inflammation and Regulates Microglia Polarization in EOC Microglial Cells—As a Potential Therapeutic Target for Neurodegenerative Dementia

Abstract: Background: Accumulating evidence has demonstrated a significant association between microglia-driven inflammation in the brain and neurodegenerative dementia. We previously showed a significant decline in CISD2 expression in mice models with advanced age. Moreover, we observed that the knockdown of CISD2 led to remarkable inflammation and mitochondrial dysfunction in neural cells. In the present study, we investigated whether CISD2 attenuation influences anti-inflammatory effects and M1-M2 polarization in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Inhibiting NADPH oxidase (Nox), which is responsible for producing ROS, drives microglia phenotype from M1 to M2 ( Babior, 1999 ; Choi et al, 2012 ). CDGSH iron-sulfur domain 2(CISD2), a longevity gene, exerts anti-inflammatory effects by inhibiting NF-κB signaling and preserving M2 microglia ( Lin, 2020 ). Toscano et al (2020) showed that postprandial triglyceride-rich lipoproteins (TRLs) could modulate microglia polarization in a fatty-acid-dependent manner: postprandial TRL-monounsaturated fatty acids promote M2 microglia polarization, whereas postprandial TRL-saturated fatty acids improve M1 microglia polarization.…”
Section: Microglia Polarization From M1 To M2mentioning
confidence: 99%
“…Inhibiting NADPH oxidase (Nox), which is responsible for producing ROS, drives microglia phenotype from M1 to M2 ( Babior, 1999 ; Choi et al, 2012 ). CDGSH iron-sulfur domain 2(CISD2), a longevity gene, exerts anti-inflammatory effects by inhibiting NF-κB signaling and preserving M2 microglia ( Lin, 2020 ). Toscano et al (2020) showed that postprandial triglyceride-rich lipoproteins (TRLs) could modulate microglia polarization in a fatty-acid-dependent manner: postprandial TRL-monounsaturated fatty acids promote M2 microglia polarization, whereas postprandial TRL-saturated fatty acids improve M1 microglia polarization.…”
Section: Microglia Polarization From M1 To M2mentioning
confidence: 99%
“…A CISD2 knockdown model using siCISD2 in immune and non-immune cells was applied to verify the potential function of CISD2. The following findings were revealed: (1) enhanced inflammatory responses (elevated production of iNOS and chemokine regulated on activation, normal T cell expressed and secreted [RANTES]), extensive mitochondrial dysfunction (including decreased mitochondrial membrane potential DeltaPsi(m) and elevated ROS release), promoted apoptosis, and decreased cell viability in neuron-like cells, SH-SY5Y [ 77 , 78 ]; and (2) augmented inflammatory reaction, as indicated in enhanced M1 microglia polarization (increased expression of TNF-α, IL-1β, iNOS, and COX2), attenuated M2 microglia phenotype (decreased expression of Arg-1, Ym1, and IL-10), and promoted apoptosis in EOC microglial cells [ 79 ].…”
Section: Cisd2 As a Nfκb Antagonist Against Inflammation And Mitocmentioning
confidence: 99%
“…Moreover, the anti-inflammatory effect of CISD2 has been shown to antagonize the activation of NFκB. Enhanced activity of NFκB p65 subunit DNA binding and subsequent nuclear translocation of NFκB p65 have been confirmed in siCISD2-transfected EOC microglial cells [ 79 ]. CISD2 inhibits NFκB signaling by acting upstream of the peroxisome proliferator-activated receptor (PPAR)-β (synonym: PPAR-δ), which is due to the decrease of PPAR-β expression shown in SH-SY5Y with CISD2 knockdown [ 80 ].…”
Section: Cisd2 As a Nfκb Antagonist Against Inflammation And Mitocmentioning
confidence: 99%
“…Our research team has demonstrated that CISD2 can block the stimulation of NFκB. Augmented DNA binding activity of the NFκB p65 subunit and nuclear translocation of NFκB p65 were verified in siCISD2-transfected EOC microglia (microglial cell lines) [ 46 ]. CISD2 slows down NFκB signaling by acting upstream of peroxisome proliferator-activated receptor (PPAR)-β [ 10 ].…”
Section: Cisd2 As a Promising Nfκb Antagonistmentioning
confidence: 99%
“…Proinflammatory responses are demonstrated by the expressive levels of iNOS and RANTES in siCISD2-transfected neuron-like cells, SH-SY5Y [ 12 , 13 ]. Augmented inflammatory reactions are revealed by an increased M1 microglia polarization (increased expression of transforming necrosis factor-α, IL-1β, iNOS, and COX2), and decreased M2 microglia phenotype (decreased expression of Arg-1, Ym1, and IL-10) in siCISD2-transfected EOC microglial cells [ 46 ].…”
Section: Cisd2 As a Promising Nfκb Antagonistmentioning
confidence: 99%